Rickettsial Infection in Animals, Humans and Ticks in Paulicéia, Brazil. (22nd January 2015) - Silveira, I.; Martins, T. F.; Olegário, M. M.; Peterka, C.; Guedes, E.; Ferreira, F.; Labruna, M. B.
Summary A previous study in Paulicéia Municipality, south‐eastern Brazil, reported 9.7% of the Amblyomma triste ticks to be infected by Rickettsia parkeri, a bacterial pathogen that causes spotted fever in humans. These A. triste ticks were shown to be associated with marsh areas, where the marsh deer Blastocerus dichotomus is a primary host for this tick species. During 2008–2009, blood serum samples were collected from 140 horses, 41 dogs, 5 opossums (Didelphis albiventris) and 26 humans in farms from Pauliceia Municipality. Ticks were collected from these animals, from vegetation and from additional wildlife in these farms. Overall, 25% (35/140) of the horses, 7.3% (3/41) of the dogs, 3.8% (1/26) of the humans and 100% (5/5) of the opossums were seroreactive (titre ≥64) to spotted fever group (SFG) Rickettsia spp. Multivariate statistical analysis indicated that horses that were allowed to forage in the marsh were 4.8 times more likely to be seroreactive to spotted fever group (SFG) Rickettsia spp than horses that did not forage in the marsh. In addition, horses that had been living in the farm for more than 8.5 years were 2.8 times more likely to be seroreactive to SFG Rickettsia spp than horses that were living for ≤8.5 years. Ticks collected from domestic animals or from vegetation included Amblyomma cajennense, Amblyomma coelebs, Amblyomma dubitatum, Dermacentor nitens and Rhipicephalus microplus. By PCR analyses, only one pool of A. coelebs ticks from the vegetation was shown to be infected by rickettsiae, for which DNA sequencing revealed to be Rickettsia amblyommii. Ticks (not tested by PCR) collected from wildlife encompassed A. cajennense and Amblyomma rotundatum on lizards (Tupinambis sp), and A. cajennense and A. triste on the bird Laterallus viridis. Our results indicate that the marsh area of Paulicéia offers risks of infection by SFG rickettsiae.